Study of Damage to Residential Buildings, Soil Geophysics and The Relationship Between the Epicentrum Distance and the Level of Damage Caused by Earthquake - Sangadji , Abdul R; Osok, Rafael M; Talakua , Silwanus M (Future Science / FSH-PH Publications, 2023)
The earthquake that occurred on September 26 2019 caused considerable damage to residential buildings in Ambon City, Central Maluku District and West Seram. This research was carried out in the villages of Liang, Tulehu and Waai, Salahutu District, Central Maluku Regency, which experienced the most damage, namely 5,406 houses were lightly damaged, 1,483 were moderately damaged, and 866 were heavily damaged. This study examines the characteristics of residential buildings, and analyzes the relationship between the level of damage to residential buildings and the distance from the epicenter. Coordinates and data on the level of damage to residential buildings (slight, moderate, very heavy) were obtained from BPBD Maluku Province, data on building characteristics including building construction, basic building conditions, building materials, building age were collected through field surveys and interviews with building owners based on damage level data building. The results showed that the level of damage to residential buildings was related to age/length, structure/construction, and materials used for building walls. The damage is even more severe if the building is old (> 20 years), the construction is boneless and unbuttoned (only the bricks are stacked), and the brick material is made of sea sand. Meanwhile, houses built with plastered masonry walls are more resistant to earthquakes. There is a relationship between the level of damage to residential buildings and the epicenter, the closer to the epicenter the damage is more severe, while the farther from the epicenter the level of damage is mild to moderate.